2014
DOI: 10.1093/sf/sot128
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Direct Investment and Economic Growth: New Evidence from Post-Socialist Transition Countries

Abstract: I n this article, we revisit classic sociological debates regarding the growth effects of Foreign Direct Investment (FDI). First, we identify a series of theoretical and empirical issues that halted sociological research on the developmental consequences of FDI. Second, we illustrate that post-socialist transition (PST) provides a historically novel opportunity to reinvigorate the debate. These countries experienced rapid industrialization but nearly zero FDI under socialism, and we can therefore observe chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 59 publications
3
46
0
1
Order By: Relevance
“…Moreover, much research in the sociology of development, adopting world-systems and dependency theoretical lenses points to negative consequences of foreign investment (Dixon & Boswell 1996;Kentor 1998Kentor , 2001de Soysa & Oneal 1999;Alderson & Nielsen 2002;Beer & Boswell 2002;Alderson 2004;Mahutga & Bandelj 2008). Further, recent studies on the link between FDI and growth have actually found a negative relationship (Herzer 2012;Curwin & Mahutga 2014). All this considered, neoliberalism that promotes FDI as a growth strategy is treated here not as based on objective economic relationships but as a policy paradigm that is constructed as more or less legitimate by states that embrace the Washington Consensus (Fourcade & Babb 2002;Mudge 2008).…”
Section: The Interplay Of Neoliberal Globalisation and Postsocialist mentioning
confidence: 99%
“…Moreover, much research in the sociology of development, adopting world-systems and dependency theoretical lenses points to negative consequences of foreign investment (Dixon & Boswell 1996;Kentor 1998Kentor , 2001de Soysa & Oneal 1999;Alderson & Nielsen 2002;Beer & Boswell 2002;Alderson 2004;Mahutga & Bandelj 2008). Further, recent studies on the link between FDI and growth have actually found a negative relationship (Herzer 2012;Curwin & Mahutga 2014). All this considered, neoliberalism that promotes FDI as a growth strategy is treated here not as based on objective economic relationships but as a policy paradigm that is constructed as more or less legitimate by states that embrace the Washington Consensus (Fourcade & Babb 2002;Mudge 2008).…”
Section: The Interplay Of Neoliberal Globalisation and Postsocialist mentioning
confidence: 99%
“…Na dopady přílivu PZI v tranzitivních ekonomikách se zaměřují např. Curwin a Mahutga (2014), Estrin a Uvalić (2013), Ichiro a Masahiro (2014), Myant a Drahokoupil (2010), v případě latinskoamerických států Falla, Olarte a Bejarano (2009), Herzer, Hühne a Nunnenkamp (2012) a Tondl a Fornero (2010).…”
Section: úVodunclassified
“…FDI contributes to the host's economic growth inter alia through the inflow of technology, enhancement of the development of enterprises and human capital and creating the competitive business environment (see for example Bevan & Estrin, ; Kurtishi‐Kastrati, ). What is more, it should increase the pace or productivity of domestic investment and provide domestic actors with access to foreign markets (Curwin & Mahutga, ). Therefore, one may conclude that if respect for human rights boosts the inflow of FDI to the given country, it should also indirectly contribute to its economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…What is more, it should increase the pace or productivity of domestic investment and provide domestic actors with access to foreign markets (Curwin & Mahutga, 2014). Therefore, one may conclude that if respect for human rights boosts the inflow of FDI to the given country, it should also indirectly contribute to its economic growth.…”
mentioning
confidence: 99%